The effect of triclosan-coated sutures on the rate of surgical site infection after hip and knee arthroplasty: a double-blind randomized controlled trial of 2546 patients. (March 2018) - Sprowson†, A. P.; Jensen, C.; Parsons, N.; Partington, P.; Emmerson, K.; Carluke, I.; Asaad, S.; Pratt, R.; Muller, S.; Ahmed, I.; Reed, M. R.
Abstract : Aims: Surgical site infection (SSI) is a common complication of surgery with an incidence of about 1% in the United Kingdom. Sutures can lead to the development of a SSI, as micro-organisms can colonize the suture as it is implanted. Triclosan-coated sutures, being antimicrobical, were developed to reduce the rate of SSI. Our aim was to assess whether triclosan-coated sutures cause a reduction in SSIs following arthroplasty of the hip and knee. Patients and Methods: This two-arm, parallel, double-blinded study involved 2546 patients undergoing elective total hip (THA) and total knee arthroplasty (TKA) at three hospitals. A total of 1323 were quasi-randomized to a standard suture group, and 1223 being quasi-randomized to the triclosan-coated suture group. The primary endpoint was the rate of SSI at 30 days postoperatively. Results: The baseline characteristics of age, gender and comorbidities were well matched in the two groups. The rates of superficial SSI were 0.8% in the control group and 0.7% in the intervention group (p = 0.651), and when deep and superficial SSIs were combined the rates were 2.5% and 1.8 (p = 0.266). The length of stay in hospital and the rates of medical complications did not differ significantly between the groups (p = 1.000). Conclusion: This trial provided no evidence that the use of triclosan-coated sutures at THA and TKA leads to a reduction in the rate of SSI. Cite this article: Bone Joint J 2018;100-B:296–302.